KIF1Bß increases ROS to mediate apoptosis and reinforces its protein expression through O2− in a positive feedback mechanism in neuroblastoma - Angelina, C.; Tan, I.; Choo, Z.; Lee, O.; Pervaiz, Shazib; Chen, Z. (Nature Publishing Group, 2017)
Relapse-prone, poor prognosis neuroblastoma is frequently characterized by deletion of chr1p36 where tumor suppressor gene KIF1Bβ resides. Interestingly, many 1p36-positive patients failed to express KIF1Bβ protein. Since altered cellular redox status has been reported to be involved in cell death and protein modification, we investigated the relationship between reactive oxygen species (ROS) and KIF1Bβ. Here, we showed that wild-type KIF1Bβ protein expression positively correlates with superoxide (O2−) and total ROS levels in neuroblastoma cells, unlike apoptotic loss-of-function KIF1Bβ mutants. Overexpression of KIF1Bβ apoptotic domain variants increases total ROS and, specifically O2−, whereas knockdown of endogenous KIF1Bβ decreases ROS and O2−. Interestingly, O2− increases KIF1Bβ protein expression, independent of the proteasomal degradation pathway. Scavenging O2− or ROS decreases KIF1Bβ protein expression and subsequent apoptosis. Moreover, treatment with investigational redox compound Gliotoxin increases O2−, KIF1Bβ protein expression, apoptosis and colony formation inhibition. Overall, our findings suggest that ROS and O2− may be important downstream effectors of KIF1Bβ-mediated apoptosis. Subsequently, O2− produced may increase KIF1Bβ protein expression in a positive feedback mechanism. Therefore, ROS and, specifically O2−, may be critical regulators of KIF1Bβ-mediated apoptosis and its protein expression in neuroblastoma.